Systems Biology Analysis of the Radiation-Attenuated Schistosome Vaccine Reveals a Role for Growth Factors in Protection and Hemostasis Inhibition in Parasite Survival - Farias, Leonardo Paiva; Vitoriano-Souza, Juliana; Cardozo, Lucas Esteves; Gama, Leonardo Dos Reis; Singh, Youvika; Miyasato, Patrícia Aoki; Almeida, Giulliana Tessarin; Rodriguez, Dunia; Barbosa, Mayra Mara Ferrari; Fernandes, Rafaela Sachetto; Barbosa, Tereza Cristina; Neto, Almiro Pires da Silva; et al. (Frontiers in Immunology, 2021)
In spite of several decades of research, an effective vaccine against schistosomiasis remains elusive. The radiation-attenuated (RA) cercarial vaccine is still the best model eliciting high protection levels, although the immune mechanisms have not yet been fully characterized. In order to identify genes and pathways underlying protection we investigated patterns of gene expression in PBMC and skin draining Lymph Nodes (LN) from mice using two exposure comparisons: vaccination with 500 attenuated cercariae versus infection with 500 normal cercariae; one versus three doses. Vaccinated mice were challenged with 120 normal parasites. Integration of PBMC and LN data from the infected group revealed early up-regulation of pathways associated with Th2 skewing and polarization of IgG antibody profiles. Additionally, hemostasis pathways were downregulated in infected mice, correlating with platelet reduction, potentially a mechanism to assist parasite migration through capillary beds. Conversely, up regulation of such mechanisms after vaccination may explain parasite blockade in the lungs. In contrast, a single exposure to attenuated parasites revealed early establishment of a Th1 bias (signaling of IL-1, IFN-γ; and Leishmania infection). Genes encoding chemokines and their receptors were more prominent in vaccinated mice, indicating an enhanced capacity for inflammation, potentially augmenting the inhibition of intravascular migration. Increasing the vaccinations from one to three did not dramatically elevate protection, but there was a clear shift towards antibody-mediated effectors. However, elements of the Th1 bias were still evident. Notable features after three vaccinations were markers of cytotoxicity (including IL-6 and NK cells) together with growth factors and their receptors (FGFR/VEGF/EGF) and the apoptosis pathway. Indeed, there is evidence for the development of anergy after three vaccinations, borne out by the limited responses detected in samples after challenge. We infer that persistence of a Th1 response puts a limit on expression of antibody-mediated mechanisms. This feature may explain the failure of multiple doses to drive protection towards sterile immunity. We suggest that the secretions of lung stage parasites would make a novel cohort of antigens for testing in protection experiments.